The Effect of Cage Enrichment on the Interior Quality of Padjadjaran Parent Stock Quail Eggs - Faiz, M. Haikal; Setiawan, Iwan; Sujana, Endang (Faculty of Animal Husbandry, Universitas Padjadjaran, 2025)
Quail housing applied in Indonesia still needs to be improved, especially in breeder quail cages. The housing system is an environmental factor that can affect egg production and quality. This study aimed to determine the effect of cage enrichment on the interior quality of hatching eggs of Padjadjaran parent stock quail. This study used 100 Padjadjaran parent stock quails divided into 80 female black and 20 male brown quails reared from January to March 2025 at the Quail Breeding Center, Faculty of Animal Husbandry, Universitas Padjadjaran. The study used an experimental with a completely randomized design (CRD) consisting of 4 treatments (T1 = wire ram cage, T2 = wire ram cage with litter, T3 = wire ram cage equipped with nesting facilities and synthetic grass, and T4 = wire ram cage with litter equipped with nesting facilities and synthetic grass). Each treatment was repeated five times and each repetition consisted of 5 quails (1 male and 4 females). Variables observed included albumen index, haugh unit, yolk index, egg pH. Data were analyzed by ANOVA followed by Duncan Multiple Range Test (DMRT). The results showed that enrichment of the cage environment did not affect on the interior quality of hatching eggs of Padjadjaran parent stock quail.